1993
DOI: 10.3354/dao015115
|View full text |Cite
|
Sign up to set email alerts
|

Further evidence for a viral etiology in plasmacytoid leukemia of Chinook salmon Oncorhynchus tshawytscha

Abstract: Plasmacytoid leukemia (PL) is an important disease of seawater pen-reared chinook salmon Oncorhynchus tshawytscha in British Columbia, Canada. The disease is caused by a n infectious agent, and the microspondium Enterocytozoon salmonis, Renibacterium salmoninarum (the cause of bacterial kidney disease. BKD), and a retrovirus have been suggested as possible causes. Experimental transmission studies were conducted to elucidate the etiology of PL and they strongly indicate that a virus is the cause of the disease… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

1994
1994
2014
2014

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 10 publications
0
9
0
Order By: Relevance
“…Bernstein (1984) also found a Type C virus in pike lymphoid tumours. Plasmacytoid leukemia caused by a retroviral agent (Kent et al 1990, Eaton & Kent 1992, Eaton et al 1993, Kent & Dawe 1993) has caused mass mortalities in cultured chinook salmon Oncorhynchus tsha wy tscha (Walbaum, 1792) (Kent et al 1990).…”
Section: Introductionmentioning
confidence: 99%
“…Bernstein (1984) also found a Type C virus in pike lymphoid tumours. Plasmacytoid leukemia caused by a retroviral agent (Kent et al 1990, Eaton & Kent 1992, Eaton et al 1993, Kent & Dawe 1993) has caused mass mortalities in cultured chinook salmon Oncorhynchus tsha wy tscha (Walbaum, 1792) (Kent et al 1990).…”
Section: Introductionmentioning
confidence: 99%
“…We presume however, that the progressive spread of lymphoblasts from sites of proliferation (principally the h d n e y and spleen) via the vasculature and their replication in distant tissues results in a leukemic-like condition which alone can b e fatal as demonstrated for the plasmacytoid leukemia of adult chinook salmon (Kent & Dawe 1990). The significant drop in hematocrits and impairment of the critical function of other organs (kidney, liver, posterior intestine) may cause death directly.…”
Section: Discussionmentioning
confidence: 99%
“…The microsporidian infections shared certain similarities to a plasmacytoid leukemia in adult chinook salmon reared in seawater as described by . However, experimental transmission studies of the plasmacytoid leukemia have not demonstrated a role of the microsporidium in the observed disease (Kent & Dawe 1990). …”
Section: Introductionmentioning
confidence: 99%
“…21 Experimental transmission trials using cell-free, ultra-filtrated inoculum from kidneys and spleens of fish with clinical plasmacytoid leukemia that had received antiprotozoal treatment resulted in successful transmission of the disease. 33 Together, these studies suggest that plasmacytoid leukemia in Chinook salmon is caused by a retrovirus, but the role of protozoal and bacterial agents as possible cofactors in the etiopathogenesis of this disease remains undetermined at this time. 34 67 The diseases manifest as cutaneous round cell tumors with a low prevalence in the summer but increased prevalence in the fall, winter, and spring.…”
Section: Chinook Salmon Plasmacytoid Leukemiamentioning
confidence: 99%
“…33,35 Plasmacytoid leukemia has been associated with a retrovirus, but coinfection with Enterocytozoon salmonis, a microsporidian parasite, and Renibacterium salmoninarum, the causative agent of bacterial kidney disease, is disproportionately common among infected fish. 33 Evaluation of renal and periocular tissues from Chinook salmon with natural and experimentally induced diseases revealed 110 nm diameter Figure 10. Skin of trunk, yellow perch discrete epidermal hyperplasia.…”
Section: Chinook Salmon Plasmacytoid Leukemiamentioning
confidence: 99%